EVALUASI KERANGKA KERJA PERENCANAAN KEBERLANGSUNGAN BISNIS PADA PT. LOTTE CHEMICAL TITAN NUSANTARA - Amirullah, Mochammad Ikmal; Subriadi, Apol Pribadi (SISFO, 2019)
Business Continuity Plan (BCP) is a company's plan to maintain its business continuity. When implementing BCP, a framework is needed to make the resulting BCP meet the needs of the company. One of the frameworks that can be used in BCP implementation is the BCP framework proposed by Yusrida. However, this framework can not be used as a standard because of the lack of empirical studies. The purpose of this research is to create BCP as well as to test the BCP framework proposed by Yusrida. This study was conducted with two scenarios. the first scenario is to implement BCP at PT. Lotte Chemical Titan Nusantara which follows the Yusrida’s BCP framework and the second scenario is to evaluate each stage of the framework. The results of this study are recommendations for improvements to the framework based on findings from the implementation of the Yusrida BCP framework at PT. Lotte Chemical Titan Nusantara.